TIPE HUMOR DALAM CERITA-CERITA PENDEK GUNAWAN TRI ATMODJO - Anwar, Saeful; Aminullah, Zakariya Pamuji (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2024)
Gunawan Tri Atmodjo's short stories are considered by many readers present humour. Many impressions are written by readers on the humorous aspect, but there is still no study that describes the humour aspect in these stories. Therefore, this study examines the types of humour in Atmodjo's stories based on a number of humour theories in literary works as presented by Louis Hasley and Matthew Kotzen. From the results of the study, it was found that there are three types of humour in Atmodjo's short stories, namely play, the formation of new words and expressions, and irony in the story. In compiling the story Atmodjo often uses the principle of deviation in normal situations. This can be seen from how he punctuates the names of the characters and the title of the work, the formation of words and expressions, and the irony in the story. These three things are built in conditions that are far from normal, both in terms of ethics (names and titles are messy and irony in the stories) and grammatical (on how words and expressions are formed). In this way, Atmodjo managed to free his readers from the emotional aspect that had been limited by ethics and grammar. Atmodjo thus consciously carried out the selection process (choosing characters and titles to play on), arranging (forming new words and expressions and arranging ironic plots), and using style (in summarizing these three things) so that the humour can be experienced and enjoyed by the reader. without leaving a message to be conveyed. The three types of humour in Atmodjo's short stories are not separate, but they support each other to build humour in the minds of the readers.